Physiology of Sporeforming Bacteria Associated with Insects II. Lipids of Vegetative Cells - Bulla, Lee A. (1970)
Lipid composition was studied in two strains each of mid-log phase cells of Bacillus thuringiensis, B. larvae, B. popilliae, B. alvei, and B. lentimorbus. Total lipids varied from 2.5 to 3.5% of the cell dry weight of B. thuringiensis to 4.3 to 5.0% of B. popilliae. Phospholipids in the organisms examined ranged from 55 to 79% of total lipids; neutral lipids averaged from 13 to 45%. Common phospholipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, and lysophosphatidylethanolamine. 1,2-Diglycerides, methyl esters, free fatty acids, and hydrocarbons were found in all the organisms studied. Branched-chain fatty acids constituted more than 50% of the total fatty acids in B. thuringiensis, B. larvae, B. popilliae, and B. alvei, whereas, in B. lentimorbus, normal-chain acids constituted more than 50%. Anteiso-C(15) (12-methyltetradeconoate) was the most abundant acid (30 to 50%) in B. alvei, B. larvae, B. popilliae, and B. lentimorbus. In contrast, B. thuringiensis contained more iso-C(13) (7%), iso-C(15) (17%), normal-C(16) (24%), and iso-C(17) (18%) than anteiso-C(15) (6%). The distribution of individual fatty acids was similar in the phospholipids and neutral lipids of each organism. However, the total amount of iso, anteiso, and normal isomers differed.